Lack of association between HLA class II alleles and in vitro replication capacities of recombinant viruses encoding HIV-1 subtype C Gag-protease from chronically infected individuals. - Wright, J; Brumme, Z; Julg, B; van der Stok, M; Mncube, Z; Gao, X; Carlson, J; Goulder, P; Walker, B; Brockman, M; Ndung'u, T (2012)
It is unknown whether favorable HLA class II alleles may attenuate HIV-1 through selection pressure in a manner similar to that of protective HLA class I alleles. We investigated the relationship between HLA class II alleles and in vitro replication capacities of recombinant viruses encoding HIV-1 subtype C Gag-protease from chronically infected individuals. No associations were found between individual alleles and lower replication capacity, suggesting no significant HIV-1 attenuation by HLA class II-restricted Gag-specific CD4(+) T cell immune pressure.